Análisis sobre la eficiencia del uso de microorganismos de montaña para potenciar la diversidad biológica de los suelos agrícolas. - Vallejos Villacis, Pablo Alejandro (2021)
At present, agriculture tends to develop clean technologies for the production of food of plant origin, this has triggered several production techniques that comply with these standards, but it can be seen that behind these techniques there is an insipient knowledge of the advantages of the application of Mountain Microorganisms (MM), for the improvement and recovery of infertile soils, must be added the incorrect use of the application of organic matter in crops, which has caused agricultural producers not to lose confidence in these techniques that seek to improve the structure and fertility of soils by increasing biological diversity and therefore the yield of agricultural production, the following bibliographic review is supported by the parameters established by scientometry, achieving the measurement and quantitative analysis of scientific production on the use of Mountain Microorganisms to enhance the diversity Biological ad of agricultural soils. This research culminates in synthesizing a bibliographic review article that, as a rule, is made up of an introduction, methodology, results and conclusion, of the information investigated and published in the last 10 years on this subject under study and its application in agriculture, resulting in 31 documents in total, where 24 documents correspond to scientific articles, 3 to books and 4 theses, documents that have allowed the writing of a bibliographic review article.